Peroxisome proliferator-activated receptor gamma and its natural agonists in the treatment of kidney diseases - Sharma, Vinesh; Patial, Vikram (Frontiers in Pharmacology, 2022)
Kidney disease is one of the leading non-communicable diseases related to tremendous health and economic burden globally. Diabetes, hypertension, obesity and cardiovascular conditions are the major risk factors for kidney disease, followed by infections, toxicity and autoimmune causes. The peroxisome proliferator-activated receptor gamma (PPAR-γ) is a ligand-activated nuclear receptor that plays an essential role in kidney physiology and disease. The synthetic agonist of PPAR-γ show a therapeutic effect in various kidney conditions; however, the associated side effect restricts their use. Therefore, there is an increasing interest in exploring natural products with PPARγ-activating potential, which can be a promising solution to developing effective and safe treatment of kidney diseases. In this article, we have reviewed the role of PPAR-γ in the pathophysiology of kidney disease and the potential of natural PPAR-γ agonists in the treatment of various kidney diseases, including acute kidney injury, diabetic kidney disease, obesity-induced nephropathy, hypertension nephropathy and IgA nephropathy. PPAR-γ is a potential target for the natural PPAR-γ agonists against kidney disease; however, more studies are required in this direction in future.